2021
DOI: 10.3389/fimmu.2021.688066
|View full text |Cite
|
Sign up to set email alerts
|

Role of Th22 Cells in the Pathogenesis of Autoimmune Diseases

Abstract: Upon antigenic stimulation, naïve CD4+T cells differentiate into different subsets and secrete various cytokines to exert biological effects. Th22 cells, a newly identified CD4+T cell subset,are distinct from the Th1, Th2 and Th17 subsets. Th22 cells secrete certain cytokines such as IL-22, IL-13 and TNF-α, but not others, such as IL-17, IL-4, or interferon-γ (IFN-γ), and they express chemokine receptors CCR4, CCR6 and CCR10. Th22 cells were initially found to play a role in skin inflammatory diseases, but rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 152 publications
(201 reference statements)
1
65
0
7
Order By: Relevance
“…Moreover, periodontal pathogens also have an ability to induce a stronger Th1 and Th17 response (Monasterio et al, 2018;Bittner-Eddy et al, 2020). Th22 cells, a new type of characterized CD4 + T cells with IL22 as the main cytokines, are associated with the pathogenesis of autoimmune diseases (Jiang et al, 2021). A positive relationship exists between Th22 and Th17 in T1D patients and Th22 might contribute to the onset of T1D (Xu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, periodontal pathogens also have an ability to induce a stronger Th1 and Th17 response (Monasterio et al, 2018;Bittner-Eddy et al, 2020). Th22 cells, a new type of characterized CD4 + T cells with IL22 as the main cytokines, are associated with the pathogenesis of autoimmune diseases (Jiang et al, 2021). A positive relationship exists between Th22 and Th17 in T1D patients and Th22 might contribute to the onset of T1D (Xu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that Th22 cells play a regulatory role in the pathogenesis of varied immune disorders, infections, and tumors ( 14 , 15 , 21 , 22 , 142 , 143 ). Here, we provided a brief summary of published research pertaining to the roles of Th22 cells in skin diseases.…”
Section: The Roles Of Th22 Cells In Skin Diseasesmentioning
confidence: 99%
“…Th22 cells have been proposed to play essential roles in autoimmune diseases including rheumatoid arthritis, inflammatory bowel diseases, asthma, multiple sclerosis, immune thrombocytopenia, nephropathy, hepatitis, thyroid diseases, and myasthenia gravis, as well as infectious diseases and tumors (14)(15)(16)(17)(18)(19)(20)(21)(22). Recently, emerging advances regarding the understanding of Th22 cells are allowing in-depth comprehension of the cutaneous immune system, which might promote the development of treatments targeting Th22 cells.…”
Section: Introductionmentioning
confidence: 99%
“…Increased production of IL-26 and IL-29 by Th17 stimulate further release of proinflammatory mediators which recruit Th1 cells into psoriatic skin lesions [ 37 , 38 ]. Increased production of IL-17 results in increased secretion of IL-19, IL-22, and IL-36 which also contribute to the development of epidermal hyperplasia [ 39 , 40 ]. IL-22 in psoriatic lesions is secreted not only by CD4 + and CD8 + T cells known as Th22 and Tc22 cells but also by Th17, mast cells, and others [ 41 ].…”
Section: Introductionmentioning
confidence: 99%